The use and comparison of a deterministic, a stochastic, and a hybrid multiple-criteria decision-making method for site selection of wind power plants: An application in Turkey. Issue 1 (February 2020) - Arı, Emin Sertaç; Gencer, Cevriye
Clean domestic energy is an attractive option, especially for developing countries. Wind has been one of the most appealing renewable energy sources for those as of the beginning of the 20th century. This study focuses on an important work item of the establishment phase of this important energy source: power plant site selection. Three approaches were examined based on multiple-criteria decision-making methods. Stochastic multi-criteria acceptability analysis (a simulation-based approach with different kinds of uncertain information), analytic hierarchy process (a conventional deterministic approach), and AHP-SMAA (a hybrid approach) were applied separately in Turkey. In terms of novelty, analyses were conducted both with (analytic hierarchy process) and without (stochastic multi-criteria acceptability analysis) the preference information of the decision makers. The unique hybrid method integrates stochastic multi-criteria acceptability analysis with analytic hierarchy process to allow the simulation-based experiments with deterministic variables. As a result of the approaches, the same region (Burhaniye-Pelitköy) showed up as the optimal site to establish wind power plants at every turn. The techniques are globally applicable as long as the computational data and all parameters are gathered completely.